2003
DOI: 10.1191/0969733003ne607oa
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Chinese, American and Japanese Nurses’ Perceptions of Ethical Role Responsibilities

Abstract: This article reports a survey of nurses in different cultural settings to reveal their perceptions of ethical role responsibilities relevant to nursing practice. Drawing on the Confucian theory of ethics, the first section attempts to understand nursing ethics in the context of multiple role relationships. The second section reports the administration of the Role Responsibilities Questionnaire (RRQ) to a sample of nurses in China (n = 413), the USA (n = 163), and Japan (n = 667). Multidimensional preference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…21 The Chinese version of the NPVS-R is composed of 26 items representing three subscales: professionalism (items 1, 2, 3, 6,7,8,9,10,11,12,14,15,16), caring (items 17,20,21,22,23,24,25), and activism (items 4,5,13,18,19,26). 18 These factors were conceptualized by Weis and Schank as essential professional nursing values and were confirmed to fit the Taiwanese culture (which is also a Chinese descendant).…”
Section: Instrumentmentioning
confidence: 99%
“…21 The Chinese version of the NPVS-R is composed of 26 items representing three subscales: professionalism (items 1, 2, 3, 6,7,8,9,10,11,12,14,15,16), caring (items 17,20,21,22,23,24,25), and activism (items 4,5,13,18,19,26). 18 These factors were conceptualized by Weis and Schank as essential professional nursing values and were confirmed to fit the Taiwanese culture (which is also a Chinese descendant).…”
Section: Instrumentmentioning
confidence: 99%
“…We add details of some of these studies to complement the above text. [66][67][68][69][70] Implications for policy makers The findings of this review have implications for policy makers at many levels. It is becoming increasingly important for governments to see health issues as being related to economic and foreign policies.…”
Section: Limitations Of the Reviewmentioning
confidence: 99%
“…4 In Sweden, the concept of integrity is brought up frequently in health care legislation, and this subject is often discussed. 31,32 Pang et al 17 found that values highly prized by American nurses were related to individual rights, much more so than in Japanese and Chinese nurses.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few cross-cultural comparisons have been performed on nurse-related ethical issues and they have mainly focused on nurses' ethical reasoning 15,16 or ethical role responsibilities. 17 We have not identified any cross-cultural study that explores the differences in the ethical dilemmas that nurses may encounter in daily practice. Thus our aim was to compare Swedish and Chinese nurses' experiences of ethical dilemmas and workplace distress to deepen our understanding of the common and unique challenges nurses encounter in different cultures, focusing on the demanding field of neuroscience nursing.…”
mentioning
confidence: 99%